High-performance rare earth permanent magnet material and preparation method and application thereof
By adding rare earth element Y and low melting point elements to the neodymium iron boron magnet, using amorphous boundary diffusion dual alloy technology and a three-dimensional high-speed mixer, combined with multi-stage heat treatment, the poor performance of neodymium iron boron magnets in the existing technology is solved and the poor performance of neodymium iron boron magnets in the existing technology is solved. Due to the high cost problem, high-performance neodymium iron boron rare earth permanent magnet material was prepared, achieving high magnetic energy accumulation and coercive force, while reducing costs.
Patent Information
- Application Number
- CN202411180180.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-20
AI Technical Summary
Existing sintered NdFeB magnets have poor performance and high cost in improving magnetic energy product (BH) max and coercive force (Hcj). In particular, it is difficult to prepare magnetic energy product greater than 54MGOe and coercive force greater than 20kOe high performance material.
By adopting amorphous boundary diffusion dual alloy technology, the grain boundary structure is optimized by adding rare earth elements Y and low melting point elements such as Zn, Sn, Cu, and Ga to the neodymium iron boron magnet, and combining with a three-dimensional high-speed mixer and multi-stage heat treatment. Prepare high-performance neodymium iron boron rare earth permanent magnet material.
The preparation of high-performance neodymium iron boron rare earth permanent magnet materials with magnetic energy product (BH) max greater than 54MGOe and coercive force (Hcj) greater than 20kOe is realized, which reduces the preparation cost and improves the performance consistency and stability of the magnets.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sintered NdFeB preparation, and in particular relates to a method for preparing rare earth NdFeB magnets by using a high-performance dual alloy technology. Background Art
[0002] Rare earth permanent magnet materials, especially sintered NdFeB materials, are widely used in wind power generation, new energy vehicles, consumer electronics, industrial robots and other fields due to their excellent magnetic properties, playing an important role in social and economic development.
[0003] With the continuous development of information technology and the electronics industry, the requirements for the integration and miniaturization of electronic products and devices are getting higher and higher, and the corresponding requirements for the magnetic energy product of sintered NdFeB rare earth permanent magnet materials used in related electronic information technology industries are getting higher and higher. At present, the magnetic energy product (BH) max of sintered NdFeB magnets used in industrial humanoid robots is required to reach more than 54MGOe, and the intrinsic coercive force is required to reach the SH level. Considering the cost issue, such high-performance products are generally produced using the grain boundary diffusion process. By diffusing the heavy rare earth terbium element, the remanence of the substrate is slightly reduced, and the coercive force is increased through the high anisotropic field of the terbium element. The increase in intrinsic coercive force can reach 8~10kOe.
[0004] For example, the patent with announcement number CN110323053B mentions that the base magnet containing high-abundance elements is mixed with at least one of oxide powder, heavy rare earth hydride powder, heavy rare earth oxyfluoride powder or heavy rare earth fluoride powder containing heavy rare earth elements to obtain a magnet with a small amount of heavy rare earth elements added to improve the coercive force of the high-abundance magnet. This patent study compares the effects of different Ce element contents and the particle size of fine powder added containing heavy rare earth elements on the coercive force of the magnet. However, due to the low magnetic energy product of the magnet in this patent, it is impossible to achieve the high magnetic energy product (BH) max greater than 54MGOe required by the air-conditioning compressor, and the average particle size D50 of the fine powder additive used is 0.1~2μm, which has uneven agglomeration and will lead to poor consistency of magnetic properties of the magnet.
[0005] The patent with announcement number CN106992053B mentions that by adding Y element to the rare earth alloy Re-Fe-B and using alloy rapid solidification and slicing technology, a texture consisting of main phase columnar crystals and intergranular phases is obtained, in which Y mainly enters the main phase to form a 2:14:1 crystal structure, and forms a Y-poor area in the rare earth-rich phase. By regulating the Y content, the alloy rapid solidification sheet can effectively adjust the distribution of rare earth elements in the main phase columnar crystals and intergranular phases in the rapid solidification sheet, laying the foundation for the subsequent preparation of rare earth permanent magnets with good performance, and can reduce the cost of subsequent magnet preparation. However, since the Y element in the patent is added during the smelting process, the Y element in the alloy sheet obtained after smelting partially exists in the 2:14:1 crystal structure, forming a (Nd / Pr / / Y)-Fe-B main phase, the magnetocrystalline anisotropy of this phase is lower than that of Pr-Fe-B, and a higher coercive force cannot be obtained.
[0006] At present, although the grain boundary diffusion process in the industry can greatly improve the comprehensive performance of magnets by diffusing low-weight-gain heavy rare earth Dy or Tb, it increases the cost of the grain boundary diffusion process, and the products after grain boundary diffusion are prone to abnormal appearance and magnetic performance quality risks. The non-grain boundary diffusion single alloy process is currently unable to produce high-performance NdFeB rare earth permanent magnet materials with a magnetic energy product (BH) max greater than 54MGOe and a coercive force greater than 20kOe. Summary of the invention
[0007] The current sintered NdFeB technology needs to use the grain boundary diffusion Dy or Tb process to prepare magnets with a magnetic energy product (BH) max greater than 54MGOe and a coercive force greater than 20kOe. Although the grain boundary diffusion process can greatly improve the magnetic properties on the basis of a lower performance magnet, it increases the cost of the grain boundary diffusion process itself, and the product after grain boundary diffusion is prone to abnormal appearance and magnetic performance quality risks. If the conventional single alloy process is used instead of the grain boundary diffusion process, it is impossible to prepare a magnet with a magnetic energy product (BH) max greater than 54MGOe and a coercive force greater than 20kOe.
[0008] In order to solve the above technical problems, the present invention adopts a non-grain boundary diffusion double alloy technology to prepare a sintered NdFeB magnet containing a certain rare earth element Ce. By studying different trace elements, it is found that rare earth element Y has a higher magnetic polarization intensity than Ce. Elements such as Zn, Sn, Cu, and Ga are non-ferromagnetic elements. By adding alloy powder with rare earth element Y into the above magnet, the magnetic energy product of Ce magnet can be greatly increased. At the same time, low melting point Zn, Sn, Cu, and Ga elements are fully distributed in the grain boundaries of the magnet, optimizing the grain boundary structure and reducing the corner defects of the main phase grains. Finally, high-performance NdFeB rare earth permanent magnet materials with a magnetic energy product (BH) max greater than 54MGOe and a coercive force greater than 20kOe can be obtained without diffusion.
[0009] The present invention provides the following technical solution: a high-performance rare earth permanent magnet material, characterized in that the raw materials include alloy component a and alloy component b; In terms of mass percentage, the alloy component A comprises: R1: 26.4~28.5wt%; Cu: 0.6~1.5wt%; Co: 2.5~5.0wt%; Ga: 0.6~1.5wt%; Tm: 0.8~1.5wt%; B: 1.02~1.2wt%; Wherein: R1 is a rare earth element, R1 includes at least Ce, Pr and RL, RL includes one or more of La, Nd and Sc, and 0<Ce / R1≤10%; Tm includes one or more of Zr, Hf and Ti; Among them: C: 0.11~0.4wt%; O: ≤0.04wt%; The rest is Fe and other inevitable elements.
[0010] In terms of mass percentage, the alloy component b includes: R2: 40~60wt%; Cu: 5~20wt%; Ga: 5~20wt%; Zn: 5~10wt%; Sn: 5~10wt%; Wherein: R2 is a rare earth element, and R2 includes a heavy rare earth element Dy and a light rare earth element Y, and 10%≤Dy / R2≤25%; The rest is Fe and other inevitable elements.
[0011] Preferably, in the alloy component a, 1≤Ce / R1≤5%. In the alloy component b, 10%≤Dy / R2≤15%.
[0012] The present invention also provides another technical solution: a method for preparing a high-performance rare earth permanent magnet material, characterized in that the preparation method is as follows: alloy component a and alloy component b are subjected to raw material smelting, hydrogen cracking, and powder making respectively to obtain alloy fine powder A with an average particle size of 2-8 μm and alloy fine powder B with an average particle size of 1-3 μm.
[0013] The A alloy fine powder and the B alloy fine powder are added into a three-dimensional high-speed mixer according to a certain weight ratio and uniformly mixed to obtain mixed C alloy fine powder.
[0014] Preferably, the weight percentage of B alloy fine powder added is 1-8wt%.
[0015] Preferably, the three-dimensional high-speed mixer is filled with nitrogen or inert gas for protection; the rotation speed of the three-dimensional high-speed mixer is 60-300 r / min, and it rotates alternately clockwise and counterclockwise at intervals of 5 minutes, and the mixing time is 30-300 minutes.
[0016] The C alloy powder is formed in a 1.5~2.5T oriented magnetic field, and then sintered at a high temperature of 1000℃~1100℃ for 3~9h; then filled with inert gas for rapid cooling to room temperature, and then first undergoes a first-level heat treatment at 850~950℃ for 2~6h; then undergoes a second-level heat treatment at 420℃~560℃ for 2~6h; and the tempered blank magnet D is obtained. The magnetic properties of the blank magnet D at room temperature meet the requirements that the magnetic energy product (BH) max is greater than 54MGOe and the coercive force (Hcj) is greater than 20kOe.
[0017] Preferably, the first stage heat treatment is performed at 900-950°C for 4-6 hours, and the second stage heat treatment is performed at 450-500°C for 4-6 hours.
[0018] The present invention also provides another technical solution: an application of a high-performance rare earth permanent magnet material, characterized in that, as a permanent magnet on the rotor of an air-conditioning compressor motor, it is embedded into the rotor core to provide a stable magnetic field so that the motor can operate stably and efficiently. It can also be applied to the field of humanoid robots, and can be applied to small motors at the joints of humanoid robots to ensure the smooth and sensitive walking of humanoid robots.
[0019] Compared with the prior art, the present invention has the following beneficial effects: by using sintered NdFeB magnets with added rare earth element Ce, rare earth element Y and other low melting point elements such as Cu, Ga, Zn, Sn are introduced through non-grain boundary diffusion double alloy technology to prepare high-performance NdFeB rare earth permanent magnet materials with a magnetic energy product (BH) max greater than 54MGOe and a coercive force greater than 20kOe. The use of low-cost rare earth elements Ce and Y can greatly reduce the preparation cost, and the residual magnetism temperature coefficient can be significantly improved. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are clearly and completely described below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0021] Embodiment 1: This embodiment provides a technical solution: a method for preparing a high-performance rare earth permanent magnet material, the steps are as follows: 1. Select the alloy composition of the base magnet a (Nd45Pr50Ce5)28FebalCo2.5Ga0.6Cu0.6Hf0.2Ti0.4Zr0.4B1.03 (wt.%), the above raw material component alloy is melted to obtain alloy sheets with an average thickness of 0.25mm.
[0022] 2. The alloy composition of the base magnet b is selected as (Dy10Y90)55FebalCu10Ga5Zn5Sn5 (wt.%), and the alloy composition of the above raw materials is smelted to obtain alloy sheets with an average thickness of 0.3 mm.
[0023] 3. The alloy a and alloy b obtained by the above smelting are subjected to hydrogen decomposition respectively, with a hydrogen absorption pressure of 0.1 MPa and a dehydrogenation temperature of 550°C. Nitrogen or inert gas protection is used during cooling to obtain alloy a particles with a size of 100-300 μm and alloy b particles with a size of 50-300 μm respectively.
[0024] 4. The alloy a and alloy b particles obtained by the above hydrogen rupture were subjected to air flow milling. 0.1% by weight of antioxidant and 0.1% by weight of lubricant were added before air flow milling. 0.2% by weight of lubricant was added during air flow milling to obtain alloy A fine powder with a particle size SMD: 3.0 μm and alloy B fine powder with a particle size SMD: 2.0 μm, respectively.
[0025] 5. Add A alloy fine powder: B alloy fine powder = 98wt%: 2wt% into a three-dimensional high-speed mixer and fill with nitrogen or inert gas protection. The high-speed mixer rotates at 200r / min, rotates clockwise and counterclockwise alternately at intervals of 5min, and the mixing time is 240min. The mixed C alloy fine powder is obtained.
[0026] 6. The C alloy fine powder was oriented and formed in a nitrogen protective atmosphere with an orientation magnetic field of 2.2T, pressed into a 30×30×30 mm compact, and after isostatic pressing, placed in a glove box filled with nitrogen to exhaust oxygen to below 200ppm for stripping.
[0027] 7. The sintering process is 1090℃×8h, and after being filled with argon and cooled to room temperature, it undergoes the first stage heat treatment at 900℃ for 4h and the second stage heat treatment at 480℃ for 4h, and then filled with argon and cooled to room temperature to obtain a block-shaped blank magnet D.
[0028] 8. Process the magnet D into Φ10×10mm, and use BH to test the magnetic properties at 20℃, and obtain the magnetic properties (BH) max: 54.8MGe, Hcj: 20.5kOe.
[0029] Embodiment 2: This embodiment provides a technical solution: a method for preparing a high-performance rare earth permanent magnet material, the steps are as follows: 1. Select the alloy composition of the base magnet a (Nd45Pr50Ce5)26.5FebalCo2.5Ga0.8Cu0.8Hf0.2Ti0.4Zr0.4B1.03 (wt.%), the above raw material component alloy is melted to obtain alloy sheets with an average thickness of 0.25mm.
[0030] 2. The alloy composition of the substrate magnet b is selected as (Dy15Y85)60FebalCu5Ga5Zn5Sn5 (wt.%), and the alloy composition of the above raw materials is smelted to obtain alloy sheets with an average thickness of 0.3 mm.
[0031] 3. The alloy a and alloy b obtained by the above smelting are subjected to hydrogen decomposition respectively, with a hydrogen absorption pressure of 0.1 MPa and a dehydrogenation temperature of 550°C. Nitrogen or inert gas protection is used during cooling to obtain alloy a particles with a size of 100-300 μm and alloy b particles with a size of 50-300 μm respectively.
[0032] 4. The alloy a and alloy b particles obtained by the above hydrogen rupture were subjected to air flow milling. 0.1% by weight of antioxidant and 0.1% by weight of lubricant were added before air flow milling. 0.2% by weight of lubricant was added during air flow milling to obtain alloy A fine powder with a particle size SMD: 3.0 μm and alloy B fine powder with a particle size SMD: 2.0 μm, respectively.
[0033] 5. Add A alloy fine powder: B alloy fine powder = 96wt%: 4wt% into a three-dimensional high-speed mixer and fill with nitrogen or inert gas protection. The high-speed mixer rotates at 220r / min, rotates clockwise and counterclockwise alternately at intervals of 5min, and the mixing time is 210min. The mixed C alloy fine powder is obtained.
[0034] 6. The C alloy fine powder is oriented and formed in a nitrogen protective atmosphere with an orientation magnetic field of 1.5T, pressed into a 30×30×30 mm compact, and after isostatic pressing, put into a glove box filled with nitrogen to exhaust oxygen to below 200ppm for stripping.
[0035] 7. The sintering process is 1085℃×9h, and after being filled with argon and cooled to room temperature, it undergoes the first stage heat treatment at 850℃ for 4h and the second stage heat treatment at 450℃ for 2h, and then filled with argon and cooled to room temperature to obtain a block-shaped blank magnet D.
[0036] 8. Process the magnet D into Φ10×10mm, and use BH to test the magnetic properties at 20℃, and obtain the magnetic properties (BH) max: 55.2MGe, Hcj: 20.2kOe.
[0037] Embodiment 3: This embodiment provides a technical solution: a method for preparing a high-performance rare earth permanent magnet material, the steps are as follows: 1. Select the alloy composition of the base magnet a (Nd45Pr50Ce5)28.5FebalCo2.5Ga0.6Cu0.6Hf0.2Ti0.4Zr0.4B1.03 (wt.%), the above raw material component alloy is melted to obtain alloy sheets with an average thickness of 0.25mm.
[0038] 2. The alloy composition of the substrate magnet b is selected as (Dy10Y90)55FebalCu5Ga5Zn5Sn5 (wt.%), and the above raw material alloy is smelted to obtain alloy sheets with an average thickness of 0.3 mm.
[0039] 3. The alloy a and alloy b obtained by the above smelting are subjected to hydrogen decomposition respectively, with a hydrogen absorption pressure of 0.1 MPa and a dehydrogenation temperature of 550°C. Nitrogen or inert gas protection is used during cooling to obtain alloy a particles with a size of 100-300 μm and alloy b particles with a size of 50-300 μm respectively.
[0040] 4. The alloy a and alloy b particles obtained by the above hydrogen rupture were subjected to air flow milling. 0.1% by weight of antioxidant and 0.1% by weight of lubricant were added before air flow milling. 0.2% by weight of lubricant was added during air flow milling to obtain alloy A fine powder with a particle size SMD: 3.0 μm and alloy B fine powder with a particle size SMD: 2.0 μm, respectively.
[0041] 5. Add A alloy fine powder: B alloy fine powder = 95wt%: 5wt% into a three-dimensional high-speed mixer and fill with nitrogen or inert gas protection. The high-speed mixer rotates at 150r / min, rotates clockwise and counterclockwise alternately at intervals of 5min, and the mixing time is 270min. The mixed C alloy fine powder is obtained.
[0042] 6. The C alloy fine powder is oriented and formed in a nitrogen protective atmosphere with an orientation magnetic field of 2.0T, pressed into a 30×30×30 mm compact, and after isostatic pressing, put into a glove box filled with nitrogen to exhaust oxygen to below 200ppm for stripping.
[0043] 7. The sintering process is 1100℃×7h, and after being filled with argon and cooled to room temperature, it undergoes a first-level heat treatment at 950℃ for 3h and a second-level heat treatment at 500℃ for 3h, and then filled with argon and cooled to room temperature to obtain a block-shaped blank magnet D.
[0044] 8. Process the magnet D into Φ10×10mm, and use BH to test the magnetic properties at 20℃, and obtain the magnetic properties (BH) max: 54.2MGe, Hcj: 21.2kOe.
[0045] Embodiment 4: This embodiment provides a technical solution: a method for preparing a high-performance rare earth permanent magnet material, the steps are as follows: 1. Select the alloy composition of the base magnet a (Nd45Pr50Ce5)28FebalCo2.5Ga0.6Cu0.6Hf0.2Ti0.4Zr0.4B1.03 (wt.%), the above raw material component alloy is melted to obtain alloy sheets with an average thickness of 0.25mm.
[0046] 2. The alloy composition of the base magnet b is selected as (Dy10Y90)40FebalCu10Ga10Zn10Sn10 (wt.%), and the above raw material alloy is smelted to obtain alloy sheets with an average thickness of 0.3 mm.
[0047] 3. The alloy a and alloy b obtained by the above smelting are subjected to hydrogen decomposition respectively, with a hydrogen absorption pressure of 0.1 MPa and a dehydrogenation temperature of 550°C. Nitrogen or inert gas protection is used during cooling to obtain alloy a particles with a size of 100-300 μm and alloy b particles with a size of 50-300 μm respectively.
[0048] 4. The alloy a and alloy b particles obtained by the above hydrogen rupture were subjected to air flow milling. 0.1% by weight of antioxidant and 0.1% by weight of lubricant were added before air flow milling. 0.2% by weight of lubricant was added during air flow milling to obtain alloy A fine powder with a particle size SMD: 3.0 μm and alloy B fine powder with a particle size SMD: 2.0 μm, respectively.
[0049] 5. Add A alloy fine powder: B alloy fine powder = 92wt%: 8wt% into a three-dimensional high-speed mixer filled with nitrogen or inert gas protection, the high-speed mixer speed is 250r / min, clockwise and counterclockwise rotation is alternated every 5min, and the mixing time is 30min. The mixed C alloy fine powder is obtained.
[0050] 6. The C alloy fine powder is oriented and formed in a nitrogen protective atmosphere with an orientation magnetic field of 1.8T, pressed into a 30×30×30 mm compact, and after isostatic pressing, put into a glove box filled with nitrogen to exhaust oxygen to below 200ppm for stripping.
[0051] 7. The sintering process is 1080℃×5h, and after being filled with argon and cooled to room temperature, it undergoes the first stage heat treatment at 920℃ for 5h and the second stage heat treatment at 560℃ for 4h, and then filled with argon and cooled to room temperature to obtain a block-shaped blank magnet D.
[0052] 8. Process the magnet D into Φ10×10mm, and use BH to test the magnetic properties at 20℃, and obtain the magnetic properties (BH) max: 54.2MGe, Hcj: 21.5kOe.
[0053] Embodiment 5: This embodiment provides a technical solution: a method for preparing a high-performance rare earth permanent magnet material, the steps are as follows: 1. Select the alloy composition of the base magnet a (Nd45Pr45Ce10)28FebalCo2.5Ga0.6Cu0.6Hf0.2Ti0.4Zr0.4B1.03 (wt.%), the above raw material component alloy is melted to obtain alloy sheets with an average thickness of 0.25mm.
[0054] 2. The alloy composition of the base magnet b is selected as (Dy25Y75)55FebalCu10Ga5Zn5Sn5 (wt.%), and the alloy composition of the above raw materials is smelted to obtain alloy sheets with an average thickness of 0.3 mm.
[0055] 3. The alloy a and alloy b obtained by the above smelting are subjected to hydrogen decomposition respectively, with a hydrogen absorption pressure of 0.1 MPa and a dehydrogenation temperature of 550°C. Nitrogen or inert gas protection is used during cooling to obtain alloy a particles with a size of 100-300 μm and alloy b particles with a size of 50-300 μm respectively.
[0056] 4. The alloy a and alloy b particles obtained by the above hydrogen rupture were subjected to air flow milling. 0.1% by weight of antioxidant and 0.1% by weight of lubricant were added before air flow milling. 0.2% by weight of lubricant was added during air flow milling to obtain alloy A fine powder with a particle size SMD: 3.0 μm and alloy B fine powder with a particle size SMD: 2.0 μm, respectively.
[0057] 5. Add A alloy fine powder: B alloy fine powder = 98.5wt%: 1.5wt% into a three-dimensional high-speed mixer and fill with nitrogen or inert gas protection. The high-speed mixer rotates at 300r / min, rotates clockwise and counterclockwise alternately at intervals of 5min, and the mixing time is 140min. The mixed C alloy fine powder is obtained.
[0058] 6. The C alloy fine powder is oriented and formed in a nitrogen protective atmosphere with an orientation magnetic field of 2.5T, pressed into a 30×30×30 mm compact, and after isostatic pressing, put into a glove box filled with nitrogen to exhaust oxygen to below 200ppm for stripping.
[0059] 7. The sintering process is 1000℃×6h, and after filling with argon and cooling to room temperature, it undergoes the first stage heat treatment at 880℃ for 2h and the second stage heat treatment at 440℃ for 5h, and then it is filled with argon and cooled to room temperature to obtain a block-shaped blank magnet D.
[0060] 8. Process the magnet D into Φ10×10mm, and use BH to test the magnetic properties at 20℃, and obtain the magnetic properties (BH) max: 54.1MGe, Hcj: 20.2kOe.
[0061] Embodiment 6: This embodiment provides a technical solution: a method for preparing a high-performance rare earth permanent magnet material, the steps are as follows: 1. Select the alloy composition of the base magnet a (Nd49Pr50Ce1)28FebalCo2.5Ga0.6Cu0.6Hf0.2Ti0.4Zr0.4B1.03 (wt.%), the above raw material component alloy is melted to obtain alloy sheets with an average thickness of 0.25mm.
[0062] 2. The alloy composition of the base magnet b is selected as (Dy10Y90)55FebalCu10Ga5Zn5Sn5 (wt.%), and the alloy composition of the above raw materials is smelted to obtain alloy sheets with an average thickness of 0.3 mm.
[0063] 3. The alloy a and alloy b obtained by the above smelting are subjected to hydrogen decomposition respectively, with a hydrogen absorption pressure of 0.1 MPa and a dehydrogenation temperature of 550°C. Nitrogen or inert gas protection is used during cooling to obtain alloy a particles with a size of 100-300 μm and alloy b particles with a size of 50-300 μm respectively.
[0064] 4. The alloy a and alloy b particles obtained by the above hydrogen rupture were subjected to air flow milling. 0.1% by weight of antioxidant and 0.1% by weight of lubricant were added before air flow milling. 0.2% by weight of lubricant was added during air flow milling to obtain alloy A fine powder with a particle size SMD: 3.0 μm and alloy B fine powder with a particle size SMD: 2.0 μm, respectively.
[0065] 5. Add A alloy fine powder: B alloy fine powder = 99wt%: 1wt% into a three-dimensional high-speed mixer and fill with nitrogen or inert gas protection. The high-speed mixer rotates at 60r / min, rotates clockwise and counterclockwise alternately at intervals of 5min, and the mixing time is 300min. The mixed C alloy fine powder is obtained.
[0066] 6. The C alloy fine powder is oriented and formed in a nitrogen protective atmosphere with an orientation magnetic field of 1.9T, pressed into a 30×30×30 mm compact, and after isostatic pressing, put into a glove box filled with nitrogen to exhaust oxygen to below 200ppm for stripping.
[0067] 7. The sintering process is 1085℃×3h, and after being filled with argon and cooled to room temperature, it undergoes the first stage heat treatment at 920℃ for 6h and the second stage heat treatment at 420℃ for 6h, and then filled with argon and cooled to room temperature to obtain a block-shaped blank magnet D.
[0068] 8. Process the magnet D into Φ10×10mm, and use BH to test the magnetic properties at 20℃, and obtain the magnetic properties (BH) max: 55.0MGe, Hcj: 21.5kOe.
[0069] Comparative Example 1: 1. According to Example 1, a single alloy component is prepared by mixing alloy A fine powder and alloy B fine powder in a weight percentage of 98wt%:2wt%. Nd12.49Pr13.7Dy0.11Y0.99Ce1.37FebalCo2.45Ga0.7Cu0.8Zn0.1Sn0.1Zr0.39Hf0.2Ti0.39B1.01 (wt.%) was melted to prepare alloy sheets with an average thickness of about 2.8 mm.
[0070] 2. The alloy obtained by the above smelting is subjected to hydrogen cracking, with a hydrogen absorption pressure of 0.1 MPa and a dehydrogenation temperature of 550°C. Nitrogen or inert gas protection is used during cooling to obtain alloy particles with a size of 100 to 300 microns.
[0071] 3. The alloy particles obtained by hydrogen rupture are subjected to air flow milling. 0.1% by weight of antioxidant and 0.1% by weight of lubricant are added before air flow milling. 0.2% by weight of lubricant is added during air flow milling to obtain alloy fine powder with a particle size SMD: 3.0 μm.
[0072] 4. Add the alloy fine powder into a three-dimensional high-speed mixer and fill it with nitrogen or inert gas for protection. The high-speed mixer rotates at 200 r / min, rotates clockwise and counterclockwise alternately at intervals of 5 minutes, and the mixing time is 240 minutes to obtain the mixed alloy fine powder.
[0073] 5. The alloy fine powder is oriented and formed in a nitrogen protective atmosphere with an orientation magnetic field of 2.2T, pressed into a 30×30×30mm billet, and after isostatic pressing, placed in a glove box filled with nitrogen to exhaust oxygen to below 200ppm for stripping.
[0074] 6. The sintering process is 1090℃×8h, and after filling with argon and cooling to room temperature, it undergoes the first stage heat treatment at 900℃ for 4h and the second stage heat treatment at 480℃ for 4h, and then it is filled with argon and cooled to room temperature to obtain a block-shaped blank magnet.
[0075] 7. The above-mentioned blank magnet was processed into Φ10×10mm, and the magnetic properties at 20℃ were tested by BH, and the magnetic properties (BH) max: 51.4MGe, Hcj: 17.2kOe were obtained.
[0076] Although embodiments of the present invention have been shown and described, it will be apparent to those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and concepts of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-performance rare earth permanent magnet material, characterized in that: The raw materials include an alloy component a and an alloy component b; In terms of mass percentage, the alloy component A comprises: R1: 26.4~28.5wt%; Cu: 0.6~1.5wt%; Co: 2.5~5.0wt%; Ga: 0.6~1.5wt%; Tm: 0.8~1.5wt%; B: 1.02~1.2wt%; Wherein: R1 is a rare earth element, R1 includes at least Ce, Pr and RL, RL includes one or more of La, Nd and Sc, and 0<Ce / R1≤10%; Tm includes one or more of Zr, Hf and Ti; The rest is Fe and other elements; In terms of mass percentage, the alloy component b includes: R2: 40~60wt%; Cu: 5~20wt%; Ga: 5~20wt%; Zn: 5~10wt%; Sn: 5~10wt%; Wherein: R2 is a rare earth element, and R2 includes a heavy rare earth element Dy and a light rare earth element Y, and 10%≤Dy / R2≤25%; The rest is Fe and other elements.
2. The high performance rare earth permanent magnet material according to claim 1, characterized in that: In the alloy component a, 1≤Ce / R1≤5%.
3. The high performance rare earth permanent magnet material according to claim 1, characterized in that: In the b alloy component: 10%≤Dy / R2≤15%.
4. The high performance rare earth permanent magnet material according to claim 1, characterized in that: In terms of mass percentage, the alloy component a also includes: C: 0.11~0.4wt%, O: ≤0.04wt%.
5. A method for preparing a high performance rare earth permanent magnetic material according to any one of claims 1 to 4, characterized in that: The preparation method is as follows: alloy component a and alloy component b are subjected to raw material smelting, hydrogen cracking, and powdering, respectively, to obtain alloy fine powder A with an average particle size of 2-8 μm and alloy fine powder B with an average particle size of 1-3 μm; Adding the A alloy fine powder and the B alloy fine powder into a three-dimensional high-speed mixer according to a certain weight ratio and mixing them uniformly to obtain a mixed C alloy fine powder; The C alloy powder is formed in a 1.5~2.5T oriented magnetic field, and then sintered at a high temperature of 1000℃~1100℃ for 3~9h; then filled with inert gas for rapid cooling to room temperature, and then first undergoes a first-level heat treatment at 850~950℃ for 2~6h; then undergoes a second-level heat treatment at 420℃~560℃ for 2~6h; and a tempered blank magnet D is obtained. The magnetic properties of the blank magnet D at room temperature meet the requirements that the magnetic energy product is greater than 54MGOe and the coercive force is greater than 20kOe.
6. The method for preparing a high performance rare earth permanent magnetic material according to claim 5, characterized in that: The three-dimensional high-speed mixer is filled with nitrogen or inert gas for protection; the rotation speed of the three-dimensional high-speed mixer is 60~300r / min, and it rotates alternately clockwise and counterclockwise at intervals of 5min, and the mixing time is 30~300min.
7. The method for preparing a high performance rare earth permanent magnetic material according to claim 5, characterized in that: The weight percentage of B alloy fine powder added is 1~8wt%.
8. The method for preparing a high performance rare earth permanent magnetic material according to claim 5, characterized in that: The first stage heat treatment is 900~950℃, and the temperature is kept at 4~6h.
9. The method for preparing a high performance rare earth permanent magnetic material according to claim 5, characterized in that: The second stage heat treatment is at 450℃~500℃, and the temperature is kept at 4~6h.
10. An application of the high performance rare earth permanent magnetic material according to any one of claims 1 to 4, characterized in that: As a permanent magnet on the rotor of the air-conditioning compressor motor, it is embedded into the rotor core to provide a stable magnetic field to enable the motor to run stably and efficiently; or, it can be applied to the field of humanoid robots and applied to small motors in the joints of humanoid robots to ensure the smooth and sensitive walking of humanoid robots.
